Is the Predictability of New-Onset Postpartum Depression Better During Pregnancy or in the Early Postpartum Period? A Prospective Study in Croatian Women. Issue 1 (2nd January 2016) - Nakić Radoš, Sandra; Herman, Radoslav; Tadinac, Meri
Abstract : The researchers' aim was to examine whether it was better to predict new-onset postpartum depression (PPD) during pregnancy or immediately after childbirth. A prospective study conducted in Croatia followed women ( N = 272) from the third trimester of pregnancy through the early postpartum period (within the first 3 postpartum days), to 6 weeks postpartum. Questionnaires on depression, anxiety, stress, coping, self-esteem, and social support were administered. Through regression analyses we showed that PPD symptoms could be equally predicted by variables from pregnancy (30.3%) and the early postpartum period (34.0%), with a small advantage of PPD prediction in the early postpartum period.